The properties of nitrogen in silicon - Alpass, C; Charles Alpass (2008)
The behaviour of nitrogen in silicon is investigated using the dislocation unlocking technique. Specimens containing well-ordered arrays of dislocations are isothermally annealed for a controlled duration, during which nitrogen segregates to and pins the dislocations. The stress required to unlock the dislocations is then measured by three-point bending at elevated temperature. By analysing the dependence of this unlocking stress on anneal duration and temperature, information about nitrogen's transport and interaction with dislocations can be deduced. Experiments are performed at anneal temperatures of 500 - 1050C using float-zone silicon with [N] = 2x10^15 cm^-3. The results are analysed to give an expression for nitrogen's effective diffusivity of D = 173,000 exp(-3.24eV/kT)cm^2 s^-1 in the 500 - 750C range, showing for the first time that nitrogen transport at low temperatures behaves in the same way as measured at higher temperatures by other groups using secondary ion mass spectrometry. If analysed in terms of monomer-dimer dissociative transport, the results give a nitrogen monomer diffusivity of D_1 = 28 exp(-(1.1 to 1.4 eV)/kT) cm^2 s^-1, which is similar to that found by another analysis in the literature. The measurements also show that nitrogen's dislocation locking strength measured at 550C is dependent on anneal temperature, peaking at 600 - 700C and falling towards zero above 1000C. The dislocation unlocking technique itself is also investigated and characterized. It is found that the measured unlocking stress is dependent on the three-point bend duration, falling with increasing duration. Analysis of these results in terms of the theory of release of dislocations from pinning points indicates that nitrogen dislocation locking is likely to be by an atomic species. This effect also has implications for the results of previous nitrogen dislocation unlocking experiments, and the technique has been modified so that a standardised set of conditions is used for every test. Other measurements show that nitrogen's dislocation locking effect is lessened by the presence of transition metal contamination, and that dislocation velocity in silicon may be affected by the nitrogen present in the material. A modified dislocation unlocking technique is developed to measure dislocation locking from near-surface ion-implanted impurities. Results from heavily N-implanted silicon show that nitrogen implantation can provide additional dislocation locking strength to that already given by the oxygen in the material. The scale of the dislocation locking effect in these experiments may provide evidence that nitrogen's effective diffusivity is reduced at high concentrations, indicating that nitrogen transport may be by a dissociative mechanism.